Patterns in recent and Holocene pollen accumulation rates across Europe - the Pollen Monitoring Programme Database as a tool for vegetation reconstruction - Abraham Vojtech; Hicks Sheila; Svobodova-Svitavska Helena; Bozilova Elissaveta; Panajiotidis Sampson; Filipova-Marinova Mariana; Jensen Christin Eldegard; Tonkov Spassimir; Pidek Irena Agnieszka; Swieta-Musznicka Joanna; Zimny Marcelina; Kvavadze Eliso; et al. (COPERNICUS GESELLSCHAFT MBH, 2022)
The collection of modern, spatially extensive pollen data is important for the interpretation of fossil pollen assemblages and the reconstruction of past vegetation communities in space and time. Modern datasets are readily available for percentage data but lacking for pollen accumulation rates (PARs). Filling this gap has been the motivation of the pollen monitoring network, whose contributors monitored pollen deposition in modified Tauber traps for several years or decades across Europe. Here we present this monitoring dataset consisting of 351 trap locations with a total of 2742 annual samples covering the period from 1981 to 2017. This dataset shows that total PAR is influenced by forest cover and climate parameters, which determine pollen productivity and correlate with latitude. Treeless vegetation produced PAR values of at least 140 grains cm(-2) yr(-1). Tree PAR increased by at least 400 grains cm(-2) yr(-1) with each 10% increase in forest cover. Pollen traps situated beyond 200 km of the distribution of a given tree species still collect occasional pollen grains of that species. The threshold of this long-distance transport differs for individual species and is generally below 60 grains cm(-2) yr(-1). Comparisons between modern and fossil PAR from the same regions show similar values. For temperate taxa, modern analogues for fossil PARs are generally found downslope or southward of the fossil sites. While we do not find modern situations comparable to fossil PAR values of some taxa (e.g. Corylus), CO2 fertilization and land use may cause high modern PARs that are not documented in the fossil record. The modern data are now publicly available in the Neotoma Paleoecology Database and aid interpretations of fossil PAR data.